Strategies for Enhancing Sharia Financial Literacy in Early Childhood Education - Poppy Indah Lestari; Rahmayati (Journal of Educational Management Research, 2026)
This study aims to analyze strategies for improving Islamic financial literacy in early childhood education institutions. Using a qualitative approach with a case study design, data were collected through non-participatory observation, in-depth interviews with key stakeholders (principal, treasurer, and teachers), and document analysis. Data analysis followed the Miles and Huberman model, involving data reduction, presentation, and conclusion drawing. The findings reveal that effective strategies include integrating Islamic financial values into children's learning activities, implementing Sharia-compliant institutional financial management, involving teachers and parents, and promoting saving and sharing practices. These strategies enhance understanding of Islamic financial literacy and improve transparency and accountability in financial management. The study concludes that Islamic financial literacy can be developed from an early age through habituation, role modeling, and Sharia-based institutional practices, although further capacity building for human resources and continuous program strengthening are needed.